Proposta de um sistema de medição de desempenho para suportar o processo de gestão estratégica da UFSCar - Ramos, Nadine (2024)
The aim of this dissertation was to propose a performance measurement system model to support the strategic management process of the Federal University of São Carlos (UFSCar). To achieve this, a literature review was conducted to describe the evolution of higher education in Brazil, conceptualize the different types of higher education institutions, list the main evaluation instruments used by regulatory bodies to assess these institutions, and outline existing performance measurement models in the literature that could be applied to such institutions. To illustrate the transition from theory to practice, a case study was conducted at the Federal University of Rio Grande do Norte (UFRN), where the use of an adapted version of the Balanced Scorecard (BSC) as support for the strategic management process was examined. Despite the extensive use of the BSC in public institutions, as identified both in the literature and in the case study, it was observed that the model is not fully compatible with this type of institution, necessitating adaptations to the BSC, including the creation of new perspectives to replace those originally defined by the model. Conversely, it was found that the Performance Prism presents elements that are better suited to the realities of public higher education institutions, even though there is a lack of studies exploring this topic on a national scale. Consequently, the proposal for UFSCar was based on the Performance Prism and was developed using UFSCar's current Institutional Development Plan (PDI) and the 2023 Management Report. The proposal is grounded in the needs and contributions of stakeholders to the institution's performance measurement process, from which information for the other model perspectives—strategies, processes, and capabilities—is derived. The development of the proposal demonstrated the alignment of the Performance Prism with UFSCar's PDI, suggesting that employing this model from the outset in the document's construction could lead to improvements in the institution's strategic management process.